PENGARUH PEMBERIAN EKSTRAK JINTAN HITAM (Nigella Sativa) 50% DAN 100% TERHADAP PENYEMBUHAN ULKUS TRAUMATIKUS PADA TIKUS WISTAR - Ayuda Nur Sukmawati; Endah Aryati E; Rahmawati Sri P; Oediani Santoso (Jurnal Medali, 2013)
Traumatic ulcer is the most common lesion in the oral mucosa. Nigella sativa has been known and proven for its therapeutical effects, such as antibacterial, antiinflammation, and analgesic. This study aimed to find out the effect of Nigella sativa extract 50% and 100% towards traumatic ulcer healing visually and histologically on wistar rats.This experimental research was done using post test design. There were 3 groups in this study, consisted of 2 treatment groups and 1 control group. Rats were ulcerated using scalpel on the tip of the lip with 5 mm diameter, then betadine was applied on the control group, and Nigella sativa extract 50% and 100% on the treatment groups with 12 hours interval. This treatment was done for 10 days. Ulcer then measured at day 0, 3rd , 7th, and 10th. The rats were sacrificed for histological examination.Result from traumatic ulcer measuring was analyzed statistically using Kruskal-Wallis test and continued with post-hoc Mann-Whitney. There was significant differences with p value < 0,05. Result from histology observation was tabulated according to categories and then analyzed.In conclusion, Nigella sativa extract has an effect towards traumatic ulcer healing visually and histologically.Â Keywords: Nigella sativa extract, traumatic ulcer, in vivo